Penerapan Metode Edutainment Dalam Meningkatkan Semangat Siswa Mata Pelajaran SKI di MTS An-Nuur Kalierang Wonosobo - Odhian Wisnu Pratama; Rifqi Muntaqo; Ali Imron (Pusat Riset dan Inovasi Nasional, 2024)
The use of learning methods used today is still an obstacle, causing various impacts. Often found is that the material presented uses a simple method in the form of lectures plus teaching materials in the form of printed books or LKS only. Research method with qualitative field. The objectives of this study. 1) To find out the concept of edutainment methods and the spirit of learning. 2) The application of edutainment learning methods in increasing students' enthusiasm for learning in SKI subjects. 3) To find out the analysis of the factors of edutainment learning methods in increasing students' enthusiasm for learning in SKI subjects. The findings show that: 1) The concept of edutainment is a step to unify the way of teaching and learning in a classroom that has a conducive and pleasant atmosphere and the spirit of learning refers to emotions and behavior to achieve learning goals and leads to passion in a learner who shows a form of seriousness and earnestness in learning. 2) The application of edutainment methods in increasing the spirit of learning in SKI subjects is based on the decline in enthusiasm for learning due to boredom and boredom. 3) Analysis of the factors of the edutainment method in increasing the enthusiasm of students learning SKI subjects examines in terms of factors in the individual himself and the beginning of educators in teaching who use simple methods.